2014
DOI: 10.1590/s1516-14392014005000050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Fe3O4 nanoparticles with perspectives in biomedical applications

Abstract: Nowadays the use of magnetic nanoparticles (MNP) in medical applications has exceeded expectations. In molecular imaging, MNP based on iron oxide coated with appropriated materials have several applications in vitro and in vivo studies. For applications in nanobiotechnology these MNP must present some characteristics such as size smaller than 100 nanometers, high magnetization values, among others. Therefore the MNP have physical and chemical properties that are specific to certain studies which must be charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 40 publications
8
40
1
2
Order By: Relevance
“…In this larger size cluster, the average Fe oct -Fe oct and Fe oct -O eq bond lengths were found to be 2.94 and 1.91Å, respectively. This is a match with the reported bond distances in the bulk magnetite (2.96 and 2.06 respectively) [67][68][69]. The difference in Fe-O bond length is mostly attributable to the Fe-O-H functions in our cluster rather than the Fe-O-Fe bonds observed in the bulk structure.…”
Section: Fesupporting
confidence: 88%
See 1 more Smart Citation
“…In this larger size cluster, the average Fe oct -Fe oct and Fe oct -O eq bond lengths were found to be 2.94 and 1.91Å, respectively. This is a match with the reported bond distances in the bulk magnetite (2.96 and 2.06 respectively) [67][68][69]. The difference in Fe-O bond length is mostly attributable to the Fe-O-H functions in our cluster rather than the Fe-O-Fe bonds observed in the bulk structure.…”
Section: Fesupporting
confidence: 88%
“…This distinction is important as differing internal geometries play an important role [48,60] in determining the behavior of magnetite-based electronic and spintronic devices. Surface alone vs internal oxidation would also have significant implications for their biomedical application [68], thus a detailed understanding of the presence of different defects in the magnetite (i.e. surface defects and impurities as well as bulk defects) is required [69].…”
Section: Fementioning
confidence: 99%
“…Although diameters measured by the three different techniques showed different average size values, this was already expected. XDR is mainly used to know the crystalline phase of the nanoparticles (maghemite or magnetite) [48], confirming the composition of maghemite, which is the final step of magnetite oxidation and thus chemically more stable [15,49]. The comparison between XRD, TEM and DLS results confirmed that NPCit have a crystalline core and an amorphous external layer.…”
Section: Discussionmentioning
confidence: 76%
“…We assumed periodic boundary conditions on all the sides of the simulation box. lognormal distribution motivated by experimental measurements [37]. Standard deviation for diameter is 0.2d m in our calculations.…”
Section: Energy Barriers and Magnetic Relaxation Timementioning
confidence: 81%